Sustainable suppley chain management and total quality management in health sector - Sayan, İlknur; Sarıcı Aytan, Yasemin (IGI Global, 2020)
ABSTRACT The supply system in health sector determines effective stock management, regular material supply, speed, and quality of maintenance and service process. Elimination of all non-value-adding activities, movements, and processes in the procurement process; minimizing errors; and increasing the efficiency of the process between the inputs and outputs of the hospital is possible by applying total quality in supply management. Effective supply chain management in health institutions improves the quality of healthcare.